2013
DOI: 10.1007/s00299-013-1489-z
|View full text |Cite
|
Sign up to set email alerts
|

The Vaccinium corymbosum FLOWERING LOCUS T-like gene (VcFT): a flowering activator reverses photoperiodic and chilling requirements in blueberry

Abstract: Blueberry is a woody perennial bush with a longer juvenile period than annual crops, requiring vernalization to flower normally. Few studies have been reported on the molecular mechanism of flowering in blueberry or other woody plants. Because FLOWERING LOCUS T (FT) from Arabidopsis thaliana plays a multifaceted role in generating mobile molecular signals to regulate plant flowering time, isolation and functional analysis of the blueberry (Vaccinium corymbosum L.) FT-like gene (VcFT) will facilitate the elucid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
50
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 62 publications
2
50
0
Order By: Relevance
“…In addition, all of the transgenic ‘VcFT-Aurora’ plants displayed dwarf phenotypes. 3 A similar phenotype has been reported in other FT -overexpressing woody plants, such as trifoliate orange, 5 plum 6 and hybrid Eucalyptus trees. 7 Early flowering driven by FT overexpression is often associated with plant dwarfing.…”
Section: Introductionsupporting
confidence: 72%
See 1 more Smart Citation
“…In addition, all of the transgenic ‘VcFT-Aurora’ plants displayed dwarf phenotypes. 3 A similar phenotype has been reported in other FT -overexpressing woody plants, such as trifoliate orange, 5 plum 6 and hybrid Eucalyptus trees. 7 Early flowering driven by FT overexpression is often associated with plant dwarfing.…”
Section: Introductionsupporting
confidence: 72%
“…Functional analyses of FT and FT -like genes have been reported in numerous studies for 20 plant species of 15 families, 13,14 including several woody plant species, such as poplar, 15–17 apple, 18,19 orange, 5 grape 20,21 and blueberry. 3 The main controversy surrounding the ‘FT-as-florigen’ hypothesis is the low mobility and stability of FT protein for long-distance transport. 22 Whether the mobile signal of ‘FT-as-florigen’ is not FT protein itself but rather other FT-derivatives with high mobility (for example, phytohormones and low-molecular-weight carbohydrates) remains to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…Remarkably, only a handful of endogenous FT genes have been functionally characterized by transgenic approaches in woody perennial species; expression under a strong constitutive promoter resulted in extremely early flowering in trifoliate orange, poplar, apple, and blueberry (Endo et al , 2005; Böhlenius et al , 2006; Hsu et al , 2006; Kotoda et al , 2010; Yamagishi et al , 2011, 2014; Song et al , 2013), and only one example of graft-transmissible early flowering has been reported in a small woody shrub, Barbados nut ( Jatropha ) (Ye et al , 2014). Even less is known about functional diversification of FT genes in woody perennials.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have concluded, FT orthologs possessing floral inductive function in woody perennials (Hisada et al, 1997; Endo et al, 2005; Böhlenius et al, 2006; Hsu et al, 2006; Carmona et al, 2007; Kotoda et al, 2010; Song et al, 2013); grasses (Yan et al, 2006; Tamaki et al, 2007; Kikuchi et al, 2009; Meng et al, 2011; Wu et al, 2013; Coelho et al, 2014); legumes (Kong et al, 2010; Ono et al, 2010; Hecht et al, 2011; Laurie et al, 2011); ornamental (Hayama et al, 2007; Hou and Yang, 2009; Imamura et al, 2011), CsFTL3 from chrysanthemum ( Chrysanthemum seticuspe ; Oda et al, 2012; Xiang et al, 2012; Li et al, 2013); and others such as BvFT2 from sugar beet ( Beta vulgaris ; Pin et al, 2010), NtFT4 from tobacco ( Nicotiana tabacum ; Harig et al, 2012), StSP3D form potato ( Solanum tuberosum ; Navarro et al, 2011), AcFT2 from onion ( Allium cepa ; Lee et al, 2013), PaFT from avocado ( Persa americana ; Ziv et al, 2014), LsFT from lettuce ( Lactuca sativa ; Fukuda et al, 2011; Above information was listed in Supplementary Table S1). Previously study suggests a conserved ancestral function of FT -like proteins in transmitting inductive signals in plants.…”
Section: Introductionmentioning
confidence: 99%